DIAMETER INCREASE OF Protium heptaphyllum (AUBL.) MARCHAND IN A SEMI-DECIDUOUS FOREST UNDER MANAGEMENT IN PIRENOPOLIS, GOIAS, BRASIL - Melo e Silva Neto, Carlos de; Venturoli, Fabio; Goncalves, Bruno Bastos [UNESP]; Ferreira, Gislene Auxiliadora (Interciencia, 2015)
The restoration process of native forests becomes increasingly important in a global context of rampant exploitation and destruction of natural resources. In this context, the search for methods to accelerate the reconstruction process of native forests becomes essential. The objective of the present study is to determine the growth rate of a native plant, Protium heptaphyllum (Aubl.) Marchand, under three forest management schemes in different vegetation types, over ten years. The study was conducted in the wildlife sanctuary of Vagafogo, municipality of Pirenopolis, Goias, Brazil. Twelve plots were established, distributed in vegetation formations ranging from a gallery forest to the 'Cerrado' sensu strictu, spanning through the forest transitions. In each plot a floristic survey was carried out and in the case of P. heptaphyllum measurements were taken from the circumference and the diameter at breast height, annual periodic increment, basal area, and mortality rate of individuals under three treatments, T1: no forest management (control), T2: withdrawal of woody species in a distance of 1m, and T3: withdrawal of woody species and large vines. T2 did not lead to significant changes in growth, as it generated a positive result in view of the increase of timber. This result highlights the importance of monitoring and management of forest areas to obtain better results in the production of forest products.